2019
DOI: 10.35563/rmp.v2i2.131
|View full text |Cite
|
Sign up to set email alerts
|

Calidad De Vida en Pacientes Con Accidente Cerebrovascular Que Acudieron a Consultorio Externo De Neurología Del Hospital Regional De Ica, Perú 2010-2011

Abstract: RESUMENObjetivo: Determinar, la percepción de calidad de vida de los pacientes que padecieron accidente cerebrovascular y que acudieron a consulta externa del servicio de Neurología en el Hospital Regional de Ica, durante los años 2010 – 2011, a través de la aplicación de la encuesta SF-36 V.2. Material y Métodos: Se realizó una investigación aplicada, no experimental, transversal, cualitativa, de nivel descriptivo. La población estuvo constituida por pacientes con diagnóstico de enfermedad cerebrovascular, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…[ 15 ] Studies on CVA in Peru are scarce; however, they have shown that patients with CVA have a significantly reduced quality of life, and the most frequent risk factor in this population is hypertension. [ 16 , 17 ] Even though early detection of intracranial atherosclerotic disease allows therapeutic intervention while CVA is still asymptomatic, [ 18 ] unfortunately, CT-based diagnostic services in low-income countries are limited and found in few high-complexity hospitals, which generates a weak response for timely identification of CVA. Although hemorrhagic CVA is not the most frequent of the 2 types, it has a higher mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Studies on CVA in Peru are scarce; however, they have shown that patients with CVA have a significantly reduced quality of life, and the most frequent risk factor in this population is hypertension. [ 16 , 17 ] Even though early detection of intracranial atherosclerotic disease allows therapeutic intervention while CVA is still asymptomatic, [ 18 ] unfortunately, CT-based diagnostic services in low-income countries are limited and found in few high-complexity hospitals, which generates a weak response for timely identification of CVA. Although hemorrhagic CVA is not the most frequent of the 2 types, it has a higher mortality rate.…”
Section: Introductionmentioning
confidence: 99%